The British Empire Revisited Through the Lens of the Eastern Question - Tchaprazov, Stoyan (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2007)
AbstractThe Bulgarians are rendered helpless in the rhetoric of the Bulgarian Agitation, a movement in Britain that produced numerous texts in response to the Ottoman massacre of thousands of Bulgarians after their uprising in April 1876. The compassion shown for the Bulgarian victims in the rhetoric of the Agitation is sincere only in moral and humane terms; open and direct political solidarity with the Bulgarians’ strident appeals for independence is missing from it. Even the morally and culturally charged pro-Agitation arguments launched by Gladstone and his followers conformed to British national interests, especially as contrasted to Bulgarian viewpoints.